Development of an Aotus nancymaae Model for Shigella Vaccine Immunogenicity and Efficacy Studies - Gregory, Michael; Kaminski, Robert W.; Lugo-Roman, Luis A.; Galvez Carrillo, Hugo; Tilley, Drake Hamilton; Baldeviano, Christian; Simons, Mark P.; Reynolds, Nathanael D.; Ranallo, Ryan T.; Suvarnapunya, Akamol E.; Venkatesan, Malabi M.; Oaks, Edwin V. (Infection and immunity, 2014)
Several animal models exist to evaluate the immunogenicity and protective efficacy of candidate Shigella vaccines. The two most widely used nonprimate models for vaccine development include a murine pulmonary challenge model and a guinea pig keratoconjunctivitis model. Nonhuman primate models exhibit clinical features and gross and microscopic colonic lesions that mimic those induced in human shigellosis. Challenge models for enterotoxigenic Escherichia coli (ETEC) and Campylobacter spp. have been successfully developed with Aotus nancymaae , and the addition of a Shigella-Aotus challenge model would facilitate the testing of combination vaccines. A series of experiments were designed to identify the dose of Shigella flexneri 2a strain 2457T that induces an attack rate of 75% in the Aotus monkey. After primary challenge, the dose required to induce an attack rate of 75% was calculated to be 1 × 10 11 CFU. Shigella -specific immune responses were low after primary challenge and subsequently boosted upon rechallenge. However, preexisting immunity derived from the primary challenge was insufficient to protect against the homologous Shigella serotype. A successive study in A. nancymaae evaluated the ability of multiple oral immunizations with live-attenuated Shigella vaccine strain SC602 to protect against challenge. After three oral immunizations, animals were challenged with S. flexneri 2a 2457T. A 70% attack rate was demonstrated in control animals, whereas animals immunized with vaccine strain SC602 were protected from challenge (efficacy of 80%; P = 0.05). The overall study results indicate that the Shigella-Aotus nancymaae challenge model may be a valuable tool for evaluating vaccine efficacy and investigating immune correlates of protection.